2009
DOI: 10.1093/schbul/sbp131
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional and Anatomical Connectivity in Schizophrenia

Abstract: The present study shows convergent fMRI and DTI findings that are consistent with the disconnection hypothesis in schizophrenia, particularly in medial frontal regions, while adding some insight of the relationship between brain disconnectivity and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
244
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(287 citation statements)
references
References 58 publications
40
244
1
2
Order By: Relevance
“…Rather than examining functional connections separately, Camchong et al [53] first integrated DTI and fc-fMRI to fully evaluate the anatomical interactions in white matter, and the functional connectivity of regions in the gray matter within the DMN for chronic schizophrenia. Patients have decreased functional connections in the mPFC during rest, and consistently, reduced white matter integrity in the mPFC.…”
Section: Anatomical and Functional Connectivity Within The Dmn In Schmentioning
confidence: 99%
See 3 more Smart Citations
“…Rather than examining functional connections separately, Camchong et al [53] first integrated DTI and fc-fMRI to fully evaluate the anatomical interactions in white matter, and the functional connectivity of regions in the gray matter within the DMN for chronic schizophrenia. Patients have decreased functional connections in the mPFC during rest, and consistently, reduced white matter integrity in the mPFC.…”
Section: Anatomical and Functional Connectivity Within The Dmn In Schmentioning
confidence: 99%
“…Patients have decreased functional connections in the mPFC during rest, and consistently, reduced white matter integrity in the mPFC. Moreover, abnormally decreased connectivity in the mPFC of patients is correlated with positive and negative symptoms, and cognitive impairments [53].…”
Section: Anatomical and Functional Connectivity Within The Dmn In Schmentioning
confidence: 99%
See 2 more Smart Citations
“…Using DTI and fMRI, Teipel et al [100] and Greicius et al [101] showed that functional connectivity across the entire DMN is based on a distinct pattern of anatomical connectivity within the cerebral white matter. In addition, some psychiatric diseases, such as schizophrenia [102] , AD [103][104][105] , and epilepsy [106] , also demonstrate a decreased WMM connectivity within the DMN. In a recent review [4] , Hulvershorn et al used a dMRI-derived network to systematically review the dysfunctional connectivity in pediatric MDD.…”
Section: Dmri Network-based Applications In Neuropsychiatric Diseasementioning
confidence: 99%